Oviposition sequence and offspring of mated and virgin females of Cotesia flavipes (Hymenoptera: Braconidae) parasitizing Diatraea saccharalis larvae (Lepidoptera: Crambidae) - Scaglia, M. [UNESP]; Chaud-netto, J. [UNESP]; Brochetto-braga, M. R. [UNESP]; Ceregato, S. A. [UNESP]; Gobbi, N. [UNESP]; Rodrigues, A. [UNESP] (Centro de Estudos de Venenos e Animais Peçonhentos, 2005)
Large scale mass rearing of natural enemies has been a mean of improving biological control in the sugarcane intensive agriculture. Among them, Cotesia flavipes, a gregarious koinobiont endoparasitoid, was imported by Brasil to control caterpillars of the sugarcane borer Diatraea saccharalis. The C. flavipes larval development depends on its association with polydnavirus, which blocks the host defense reaction. To verify if the oviposition sequence (1st, 2nd or 3rd) and the female condition (mated or virgin) interfere in the number of C. flavipes descendents, 4th instar caterpillars of D. saccharalis were parasitized. Analysis of the data showed that: a) there is an inverse correlation between the parasitism efficiency and the host reaction (encapsulation); b) the number of caterpillars parasitized by virgin females that released parasitoid larvae in the period from 12 to 15 days was higher than that of caterpillars parasitized by mated females; c) a slight difference between mated and virgin females in relation to the parasitim success was observed; and d) the number of encapsulated parasitoid larvae was higher than that of eggs, suggesting that eggs have a better capacity to overcome the host reaction. In this study, the viability of C. flavipes eggs and larvae in the non-specific host D. saccharalis could be correlated with the oviposition sequence and the female condition.
Keywords: Cotesia flavipes; Diatraea saccharalis; oviposition sequence; encapsulation; chrysalises; parasitism